2018
DOI: 10.3389/fnagi.2018.00180
|View full text |Cite
|
Sign up to set email alerts
|

APOE and Alzheimer’s Disease: Neuroimaging of Metabolic and Cerebrovascular Dysfunction

Abstract: Apolipoprotein E4 (ApoE4) is the strongest genetic risk factor for late onset Alzheimer’s Disease (AD), and is associated with impairments in cerebral metabolism and cerebrovascular function. A substantial body of literature now points to E4 as a driver of multiple impairments seen in AD, including blunted brain insulin signaling, mismanagement of brain cholesterol and fatty acids, reductions in blood brain barrier (BBB) integrity, and decreased cerebral glucose uptake. Various neuroimaging techniques, in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 97 publications
3
37
0
Order By: Relevance
“…The current finding that apoE4 carriers are impaired relative to apoE3 carriers in cognitive parameters is consistent with previous studies in mice [81][82][83] and humans [84][85][86]. The fact that the HFD impaired apoE3 mice is consistent with many studies that have shown that WT mice are impaired following the HFD in cognitive [87,88], sensory [89], and motor paradigms [89].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current finding that apoE4 carriers are impaired relative to apoE3 carriers in cognitive parameters is consistent with previous studies in mice [81][82][83] and humans [84][85][86]. The fact that the HFD impaired apoE3 mice is consistent with many studies that have shown that WT mice are impaired following the HFD in cognitive [87,88], sensory [89], and motor paradigms [89].…”
Section: Discussionsupporting
confidence: 92%
“…This test was performed as described in [81,106] and is based on the natural tendency of rodents to investigate a novel object. For the habituation phase, the mice were first placed in an arena (50 × 50 cm with 40 cm high walls) in the absence of objects.…”
Section: Short-term Memory Measurementsmentioning
confidence: 99%
“…We found E4 astrocytes to exhibit a lower OCR compared to E3 at all time points (Figure 4E). This lower OCR is likely primarily due to a decreased rate of glucose oxidation, as E4 is strongly associated with a phenotype of glucose hypometabolism [4,37]. When we specifically calculated the contribution of FA oxidation to OCR by comparing basal OCR in palmitate treated versus BSA treated astrocytes, we found that E4 astrocytes utilize significantly less exogenously supplied FA as part of their basal respiration (Figure 4F).…”
Section: Resultsmentioning
confidence: 97%
“…In addition to established effects on AD neuropathology, APOE genotype is also recognized as a strong modulator of cerebral metabolism [3,4,5,6]. In fact, cognitively normal E4+ individuals demonstrate alterations in cerebral fatty acid (FA) and carbohydrate metabolism congruent with AD patients [4,7]. Understanding the metabolic effects of apoE in the brain may be a critical step in discovering the underlying mechanism(s) of E4-driven AD risk.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, polymorphism of ApoE allele, especially ApoE ε4, attributes to risk of AD development by increasing Aβ and Tau aggregation, whereas ApoE ε2 exhibits protective effects on risk of AD development (Verghese et al, 2011). Moreover, ApoE ε4 induces dysregulation of cerebral metabolism by decreasing lipid and glucose metabolism (Brandon et al, 2018). Interestingly, the control of insulin and plasma glucose by ghrelin administration can vary depending on the details of administration (i.e., duration, route, and dose) (Nieminen and Mustonen, 2004;Theander-Carrillo et al, 2006;Barazzoni et al, 2007a;Goshadrou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%